Aggression and emotion: Anger, not general negative affect, predicts desire to aggress. (October 2016) - Wyckoff, Joy P.
Abstract: Many psychologists have theorized that negative emotions lead to aggression but what contexts trigger these emotions and how these emotions predict aggression remains unclear. According to the recalibrational theory of anger, anger is triggered when an interaction partner places a low relational evaluation on oneself, which motivates aggression (Sell, Tooby, & Cosmides, 2009). The present studies test the theory that anger mediates aggression and examine how other negative emotions relate to aggression. In Study 1, anger fully mediated the relationship between self-perceived mate value and self-reported direct aggression. In Study 2, anger partially mediated the relationship between relative mate value and self-reported desire to use direct aggression. Anger also partially mediated the relationship between relative mate value and self-reported desire to use indirect aggression. Further, anger fully mediated the relationship between self-perceived strength and self-reported desire to use direct aggression. For men, anger fully mediated the relationship between self-perceived mate value and self-reported desire to use indirect aggression. However, fear, embarrassment, and sadness did not predict aggression in any analyses. Results indicate that anger, but not negative emotions more generally, predict self-reported aggression. Highlights: Anger partially mediated the relationship between relative mate value and direct aggression. Anger partially mediated the relationship between relative mate value and indirect aggression. Anger fully mediated the relationship between strength and direct aggression. Anger mediated the relationship between mate value and direct aggression in men and women, and indirect aggression in men. Fear, sadness, and embarrassment did not mediate a relationship with direct or indirect aggression.